Efectividad de las técnicas respiratorias en la recuperación de pacientes con neumonía por covid-19, hospital general IESS Babahoyo. Diciembre 2022- mayo 2023. - Arias Alvarado, Jorge Andrés (2023)
In the present investigation, it refers to the effectiveness of the use of respiratory techniques applied in patients with pneumonia by Covid 19 of the IESS Babahoyo General Hospital, as these contribute greatly to minimizing complications and a successful recovery in patients with this type of pathology. It is inherent as a health professional, especially in the area of respiratory therapy, to have knowledge and experiences in the application of respiratory physiotherapy techniques, in such a way as to be able to solve complications and needs that hospitalized patients develop, thus minimizing the chances of morbidity and mortality. The general objective of the project is to: determine the percentage of effectiveness of respiratory therapy techniques applied to patients recovering from COVID-19 pneumonia at the IESS Babahoyo Hospital. Period December 2022– May 2023. In conclusion, it can be highlighted that the use of respiratory techniques are a useful tool that are of enormous help to prevent exacerbation of various diseases that affect the respiratory system, such as pneumonia developed after COVID-19 becomes fatal, if it is not treated in time.